2021
DOI: 10.1016/j.surfcoat.2020.126557
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional homogeneous calcium phosphate coatings: Toward antibacterial and cell adhesive titanium scaffolds

Abstract: ARTICLE INFO Titaniwn scaffolds Calciwn phosphate coating Chlorhexidine dig)uconate Antibacterial Biocompatibility On-ep pulse electrodeposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…As a common antibacterial agent, chlorhexidine has a broad-spectrum bactericidal effect and low drug resistance. Loading chlorhexidine into bioceramic-based composite scaffolds gave the scaffolds strong antibacterial properties, indicating the potential for biomedical applications, particularly controlled drug delivery in dentistry [ 53 , 54 ]. Berberine, an alkaloid component extracted from botanicals, has been long used as a heat-clearing, detoxifying and antibacterial drug.…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%
“…As a common antibacterial agent, chlorhexidine has a broad-spectrum bactericidal effect and low drug resistance. Loading chlorhexidine into bioceramic-based composite scaffolds gave the scaffolds strong antibacterial properties, indicating the potential for biomedical applications, particularly controlled drug delivery in dentistry [ 53 , 54 ]. Berberine, an alkaloid component extracted from botanicals, has been long used as a heat-clearing, detoxifying and antibacterial drug.…”
Section: Bioceramic-based Scaffolds With Drug-induced Antibacterial F...mentioning
confidence: 99%
“…The apatite-forming ability test and in vitro cell culture assay resulted in the highest apatite formation and significantly greater adhesion and differentiation of mesenchymal stem cells (MSCs) on the HT/AH-porous Ti6Al4V compared to the scaffolds without HAp-coating [200]. In [217], the pulsed reverse electrodeposition was used to obtain calcium phosphate (CaP) coatings doped with chlorhexidine digluconate on an additively manufactured CP-Ti scaffold. The result showed the surface of scaffolds was covered by plate-like and whisker-like calcium phosphate crystals with a Ca/P ratio of 1.30.…”
Section: Structural Factors Influencing the Mechanical Propertiesmentioning
confidence: 99%
“…After the 7th day of in vitro assay, the cells cultured on the 3D-Ti-NTs-MBG scaffolds presented no significantly different proliferation rates, when compared with those on the 3D-Ti-NTs scaffolds. In [217], cell behavior on CP-Ti scaffold coated by calcium phosphate (CaP) showed that the addition of CHX decreased cell adhesion in comparison to the scaffolds with CaP coatings.…”
Section: Osteoconductive and Osteoinductive Properties 721 In Vitrmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium and titanium alloys are also intensively used in a large number of applications, due to their outstanding corrosion resistance, great mechanical properties, and good biocompatibility [54,96]. A problem with these alloys as biomaterials is that they may be a cause of thrombosis when they come into contact with blood, as in the case of coronary stents, and anticoagulation medication is usually prescribed to prevent this from happening.…”
Section: Trends In Enhancing Coatings Performances On Cocr Alloys and Other Metallic Alloys (Including High-entropy Alloys)mentioning
confidence: 99%